Applied Informatics - Xu, Lei
Applied Informatics covers the theory and application of informatics in various scientific, technological, engineering and social fields. Aiming to inspire new multidisciplinary research, the journal acts as an integrative venue that collects high-quality original research papers and reviews on various aspects of applied informatics, with the foundations of informatics (information theory, statistical modeling, machine learning, etc) as the driving core and the interactions between essential realms as the promoting focuses; particularly important are the interactions between (a) life sciences (bioinformatics, medical informatics, bioengineering, etc); and (b) intelligence sciences (neural and cognitive informatics, multimedia, pattern recognition, etc), and (c) community sciences (social networks, affective computing, big data analytics, etc).